Multivariate MIMO FIR inverses - Rajagopal, Ravikiran (IEEE transactions on image processing : a publication of the IEEE Signal Processing Society, 2003)
The problem of computing exact finite impulse response (FIR) inverses for multivariate multiple-input multiple-output (MIMO) FIR systems is considered. Necessary and sufficient conditions for invertibility are given, along with computation techniques. Random systems and structured systems are defined. Necessary and sufficient conditions for the almost sure invertibility of structured random systems are derived. Bounds on the orders of the inverse filters are computed